2008
DOI: 10.1007/s11547-008-0333-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of lipodystrophy in HIV-1-infected patients

Abstract: We consider the ratio between visceral adipose tissue and subcutaneous adipose tissue and the thickness of malar fat to be the most useful ultrasonographic parameters for the early diagnosis of lipodystrophy in HIV-infected patients on highly active antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Alike other authors that have reported similar correlation between subjective perceptions and sonography in the subcutaneous and visceral body fat compartments, 15,17,18,27 our study estimated a kappa statistic of substantial agreement between the findings obtained by sonographic measurements and clinical LD. Thinner facial fat compartment, upper arm, and subcutaneous abdomen fat as well as thicker visceral adiposity were associated with clinical LD, as well as sex and BMI.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Alike other authors that have reported similar correlation between subjective perceptions and sonography in the subcutaneous and visceral body fat compartments, 15,17,18,27 our study estimated a kappa statistic of substantial agreement between the findings obtained by sonographic measurements and clinical LD. Thinner facial fat compartment, upper arm, and subcutaneous abdomen fat as well as thicker visceral adiposity were associated with clinical LD, as well as sex and BMI.…”
Section: Discussionsupporting
confidence: 87%
“…15 Other studies, using ROC curves to compute the accuracy of the sonography assessment, found specific, separate cutoffs for each one of the body compartments involved in the definition of LD. 14,[16][17][18] These studies also support the use of sonography to assess body fat compartments in HIV-infected persons. Since they did not fit a model to compute ROC curves, we cannot compare the accuracy of these tests with our results.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…22,23 Visceral obesity can be evaluated by different techniques, including CT, [24][25][26] MRI, 27-29 and US. 10,11,[30][31][32][33] However CT and MRI are expensive and employ ionizing radiations, so they are not suitable for large-scale use. US is simple, rapid, available, and safe and is low cost when compared with CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnoses of visceral obesity were based on sonographic measured PRFD/BMI ratio >0.22. Grima et al 10 observed that this value could be considered a potential parameter to assess a visceral fat accumulation in HIV-1-infected patients.…”
Section: Study Populationmentioning
confidence: 99%